Uma educação invisível - Queiroz, João Paulo, 1966- (2018)
Artistic education faces the risk of gradual disappearance from its formal education habitat. At the same time the civil society increasingly demands more art-educated public in the context of the institutions that depend on the success of audiences and visitors. It is a contradiction of terms that appear to be originating a “cognitive liberalism:” this seems to be a paradigm to remain. These themes are reflected in different ways in the thirteenth issue of the Revista Matéria-Prima gathering 16 original articles